Trends and projections in cause-specific mortality among patients with colorectal cancer in the United States, 1999–2040 - Ziyan He; Yadong Chen; Yuxing Hu; Jiajia Lin; Yifan Wang; Caiqiu Deng; Yue Cong; Jiaming Liu; Rui Zhou; Yihan He; Fangfang Hou; Haibo Zhang (Frontiers in Public Health, 2026)
Background As CRC survival improves, the shifting contributions of metastatic and non-cancer causes to mortality remain poorly characterized, with implications for survivorship care and public health policy. This study aimed to examine temporal trends in CRC mortality with selected contributing conditions from 1999 to 2023 and project rates through 2040 across demographic and geographic subgroups in the United States. Methods This population-based cohort study utilized mortality data from the Centers for Disease Control and Prevention Wide-ranging Online Data for Epidemiologic Research (CDC WONDER) database. The study included 1,323,609 US residents aged 25 years or older who died from 1999 through 2023 with colorectal cancer listed as the underlying cause of death. We analyzed selected contributing conditions recorded in the multiple cause-of-death field, including heart failure, ischemic heart disease, liver metastasis, lung metastasis, pulmonary embolism, and sepsis. Age-adjusted mortality rates (AAMRs) were calculated per 100,000 persons. Temporal trends were analyzed using Joinpoint regression to estimate annual percent change (APC) and average annual percent change (AAPC). Future mortality rates were projected to 2040 using autoregressive integrated moving average (ARIMA) modeling. Results Overall CRC AAMR declined from 32.06 in 1999 to 19.57 in 2023 (AAPC,−2.08%). Recent significant increases were observed in liver metastasis mortality from 2016 to 2023 (APC: 2.89%), lung metastasis mortality from 2017 to 2023 (APC: 2.08%), pulmonary embolism mortality from 2012 to 2023 (APC: 3.59%), and heart failure mortality from 2013 to 2023 (APC: 3.16%). These trends were most pronounced among adults aged 35–64 years, non-Hispanic Black individuals, and residents of the Southern US. Model-based projections indicate that overall lung metastasis mortality will continue to increase through 2040, whereas liver metastasis mortality will peak in 2028 and subsequently decline. In pre-pandemic sensitivity analyses, the post-2012 increase in PE mortality persisted, whereas recent increases in IHD, HF, liver metastasis, and sepsis mortality were attenuated or no longer statistically significant. Conclusions Despite declining overall CRC mortality, recent increases were observed in several metastatic and noncancer contributing conditions. However, pre-pandemic sensitivity analyses suggested that some late-period changes may have been amplified during the COVID-19 era, whereas the increase in PE mortality clearly preceded the pandemic.